A Survey of Extraction Chromatographic f-Element Separations Developed by E. P. Horwitz. Issue 3 (15th April 2020) - Bertelsen, Erin R.; Jackson, Jessica A.; Shafer, Jenifer C.
ABSTRACT: An extensive suite of f -element extraction chromatographic (EXC) resins was developed by E. Philip Horwitz and his groups at Argonne National Laboratory, PG Research Foundation, and Eichrom Technologies, Inc. The separation character of the specific resins is largely determined by the extractant physisorbed on the solid support. Modelled after solvent extraction systems employing the same extractants, TEVA, UTEVA, TRU, DGA, Actinide, and the LN family of resins have become benchmarks for research comparisons and are available for commercial applications. The f -elements separations community has applied these resins in a multitude of analytical fields from nuclear medicine isotope production to environmental analysis. As the field of extraction chromatography begins to explore innovative solid supports and ingenuity in the applicability of the EXC resins themselves, the tremendous contributions of Horwitz must be considered. This review examines the EXC materials developed by Horwitz, specifically for f -elements, and discusses separation schemes and process development.